Reverse transcriptase inhibitors diminish systemic proinflammatory responses to bacterial pathogens - Karthik Hullahalli; Katherine G. Dailey; Ryan Acbay; Masataka Suzuki; George I. Balazs; Matthew K. Waldor (mBio)
ABSTRACT Bacterial infections can induce exuberant immune responses that can damage host tissues. Previously, we demonstrated that systemic Escherichia coli infection in mice causes tissue damage in the liver. This liver necrosis is associated with the expression of endogenous retroviruses, chromosomally integrated retroviruses that encode a reverse transcriptase. Furthermore, nucleotide/nucleoside reverse transcriptase inhibitors (NRTIs) completely prevent tissue damage and subsequent bacterial growth within necrotic lesions. Since liver necrosis is linked to heightened systemic inflammatory responses, we hypothesized that NRTIs diminish inflammation caused by E. coli infection and may also have broad impacts on the systemic immune response to bacterial pathogens. Here, we tested this hypothesis by characterizing the effects of NRTIs on the innate immune response to bacteria. In the liver, NRTI administration following E. coli inoculation reduced the expression of a large repertoire of proinflammatory transcripts. NRTIs also had systemic anti-inflammatory effects, including reducing proinflammatory cytokine levels in serum in response to E. coli in different mouse strains. The anti-inflammatory effects of NRTIs were also apparent in response to lipopolysaccharide (LPS) and Staphylococcus aureus, suggesting that the molecular mechanisms underlying the immunomodulatory functions of NRTIs are likely conserved across distinct immune signaling pathways. Moreover, in a model of lethal LPS shock, NRTI administration prevented hypothermia and death. Together, our observations reveal that NRTIs can potently impede systemic inflammatory responses during Gram-positive and Gram-negative bacterial infections. Our findings lay the groundwork for further investigation of the therapeutic scope of NRTIs and the mechanisms underlying their anti-inflammatory effects across non-retroviral infectious diseases.IMPORTANCEInflammatory responses are critical for host control of bacterial infection, but excessive inflammation can damage host tissues and lead to sepsis. Understanding how innate immune responses are controlled during infection is important for developing new approaches to dampen excessive inflammation. In previous work, we found that tissue damage caused by excessive inflammatory responses may be driven by endogenous reverse transcriptases. Here we demonstrate that treatment of mice with reverse transcriptase inhibitors leads to broad reductions in systemic proinflammatory responses during bacterial infections and can protect mice from acute death in a lethal model of sepsis. Our findings indicate that uncovering the mechanisms underlying the anti-inflammatory functions of reverse transcriptase inhibitors may lead to new therapeutics for bacterial infectious diseases.